Evaluation of Cow Milk Quality with Lactoscan Technology, Alcohol Test, and Reductase at the Batu Livestock Training Center (BBPP) - Madeira, Anggrenita Maria Gita; Kamlasi, Yohana (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
Evaluation of cow's milk quality is very important to ensure safety and nutritional content in accordance with standards. This research was conducted at the Batu Livestock Training Center (BBPP) using three main testing methods, namely Lactoscan technology, 70% alcohol test, and reductase test. The results showed that the quality of the milk tested was still within acceptable standard limits. The Lactoscan method provided a quick analysis of milk composition, including fat, protein and solid non-fat (SNF) content. The 70% alcohol test indicated good protein stability, while the reductase test indicated acceptable levels of microbial population in the milk but required improved sanitation in the milking and storage processes. This study confirms the importance of implementing hygienic standards in milk production to improve product competitiveness in domestic and international markets.